Austrian College Students’ Experiences With Digital Media Learning During the First COVID-19 Lockdown - Kovacs, Carrie; Jadin, Tanja; Ortner, Christina (Frontiers in Psychology, 2022)
In 2020, the COVID-19 pandemic forced many nations to shut down schools and universities, catapulting teachers and students into a new, challenging situation of 100% distance learning. To explore how the shift to full distance learning represented a break with previous teaching, we asked Austrian students (n = 874, 65% female, 34% male) which digital media they used before and during the first Corona lockdown, as well as which tools they wanted to use in the future. Students additionally reported on their attitudes and experiences with online learning. Results showed that students used certain tools, such as video, audio, e-assessments and web conferencing systems, much more often during lockdown than they had before. Their use of classic digital media such as e-mail, social communication tools such as chat or online forums, and other interactive tools such as wikis or educational games, hardly changed at all. Their attitudes toward multimedia learning were positively related to their media use. In their open responses (n = 137), students identified advantages of online learning (flexibility, self-directed learning), as well as disadvantages (limited social interaction) and challenges (motivation, self-discipline). As a group, they also expressed a clear preference for a balanced combination of online- and offline teaching in the future. However, individual students did prefer fully online or offline learning modes, depending on their personal circumstances and educational goals. We view this as a call to researchers and educators alike to explore ways in which the advantages of online and face-to-face learning can best be combined to meet the changed needs and expectations of organizations, students and teachers in a future “after Corona.”